The rediscovery of the types of Whartonia pachywhartoni Vercammen-Grandjean, 1966 (Trombidiformes: Leeuwenhoekiidae) with new records in Brazil - Bassini-Silva, Ricardo (2025)
Whartonia Ewing is associated with bats, and in Brazil, there are three species recorded, Whartonia nudosetosa (Wharton), Whartonia pachywhartoni Vercammen-Grandjean, and Whartonia parauapebensis Bassini-Silva & Jacinavicius. Since the species description was first published in 1966, the whereabouts of the type series of W. pachywhartoni has been lost. Because of this, subsequent identifications always carried some doubt. After visiting the USNM collection, two paratypes were found. Here, we provide a detailed redescription of this species based on the newly found paratypes and DIC images of recently collected material to help with future identifications. Also, new records for the state of Rio de Janeiro, Brazil, are added for W. pachywhartoni.